Effect of Polishing Systems on the Surface Roughness of Nano-Hybrid and Nano-Filling Composite Resins: A Systematic Review - Robinson Jaramillo-Cartagena; Eider J. López-Galeano; Federico Latorre-Correa; Andrés A. Agudelo-Suárez (MDPI AG, 2021)
Background: The polishing of surface roughness is an important characteristic of composite resins and is directly related to the longevity of the restoration and patient comfort. Different polishing systems utilize different protocols, as reported in the literature. This systematic review (SR) aimed to synthesize and analyze the available scientific evidence about the effect of polishing systems on the surface roughness of nano-hybrid and nano-filling composite resins. Methods: The study protocol of this SR was registered at the International Prospective Register of Systematic Reviews -PROSPERO- (CRD4201705653). A search was conducted in PubMed-Medline, Scopus, LILACS, EMBASE, for the period 2007-2020. Quality appraisal and a descriptive analysis of the papers that met the inclusion criteria were conducted. Results: 18 records were included. Seven polishing systems (PS) of one step were found, seven PS of two steps, eight PS of three steps, three PS of four steps, and four PS of five steps. Polishing protocols (PP) varied, with application times ranging from 10 s to 60 s with speeds between 10,000 and 30,000 RPM. Regarding composition, the aluminum oxide was one of the most important components used to achieve a smooth surface. Conclusions: Multistep polishing systems were the most effective (i.e., Astropol and Sof-Lex Discs).